Synthesis, Spectral Studies, Antimicrobial Activity and Crystal Structures of Phosphaza-Lariat Ethers - Ozay, Hava; Yildiz, Mustafa; Unver, Huseyin; Dulger, Basaran (Asian Journal of Chemistry, 2011)
Phosphaza-lariat ethers, which are known as 2,2-[4,4'-(2,2'-oxybis(ethane-2,1- diyl)bis(oxy))dianilino]-4,4,6,6-tetrachlorocyclo-2l5,4l5,6l5-triphosphazatriene(spiro) (1), 2,2- [4,4'-(2,2'-(ethane-1,2-diylbis(oxy))bis(ethane-2,1-diyl))bis(oxy)dianilino]-4,4,6,6- tetrachlorocyclo-2l5,4l5,6l5-triphosphazatriene(spiro) (2) and 2,2-[4,4'-(2,2'-(ethane-1,2- diylbis(oxy))bis(ethane-2,1-diyl))bis(oxy)dianilino]-4,4-bis(tert-butylamino)-6,6-dichlorocyclo- 2l5,4l5,6l5-triphosphazatriene (3) have been synthesized. The structures of the compounds (1, 2 and 3) are characterized by elemental analysis, IR, 1H, 13C, 31P NMR and mass spectroscopic techniques. The antimicrobial activities of the compounds have been screened in vitro against the organisms. The structures of the compounds 1, 2 and 3 have also been examined by means of cyrstallographically. The compounds 1, 2 and 3 crystallize in the orthorhombic space group Pbca, hexagonal space group P43212 and tetragonal space group P42/n, respectively. They have unit cell parameters: a = 15.607(1), 10.6723(2) and 26.0308(9), b = 15.667(2), 10.6723(2) and 26.0308(9), c = 19.481(3), 23.3633(6) and 10.6033(4) Å, V = 4763.4(1), 2661.03(1) and 7184.8(4) Å3, Dx = 1.570, 3.031 and 1.258 g cm-3 and Z = 8, 8 and 8, respectively.